2004
DOI: 10.1055/s-2004-827174
|View full text |Cite
|
Sign up to set email alerts
|

High Dose Antipsychotic Use in Schizophrenia: Findings of the REAP (Research on East Asia Psychotropic Prescriptions) Study

Abstract: This survey revealed that high antipsychotic dosing is not an uncommon practice in East Asia. It behooves the prescribing clinicians to constantly reevaluate the rationale for such a practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 20 publications
2
39
0
Order By: Relevance
“…Results: The RLAI group showed significantly increased positive score of Positive and Negative Syndrome Scale (PANSS) than the risperidone group (0.72 3.52 vs. ±1. 24 3.81, p = 0.022), but without significance difference for the PANSS total, negative and general psychopathology scores. The RLAI group also showed a significantly improved Udvalg for Kliniske Undersogelser (UKU) Scale (p = 0.037), social life domains of ShortFrom Health Survey (SF-36) (p = 0.011), and reduced prolactin level (p = 0.001).…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Results: The RLAI group showed significantly increased positive score of Positive and Negative Syndrome Scale (PANSS) than the risperidone group (0.72 3.52 vs. ±1. 24 3.81, p = 0.022), but without significance difference for the PANSS total, negative and general psychopathology scores. The RLAI group also showed a significantly improved Udvalg for Kliniske Undersogelser (UKU) Scale (p = 0.037), social life domains of ShortFrom Health Survey (SF-36) (p = 0.011), and reduced prolactin level (p = 0.001).…”
mentioning
confidence: 63%
“…Our result showed the VAS rating of pain over the injection area was mild. Patients who are treated with RLAI will benefit from knowing that they are less likely to experience pain, an injection site reaction, or breakthrough EPS than compared with conventional depot therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic data and use of psychotropic drugs were collected from the case notes and confirmed during the diagnostic interview. Doses of antipsychotic drugs were converted to chlorpromazine equivalents (CPZeq; Kane, 1996;Sim et al, 2004b).…”
Section: Data Collectionmentioning
confidence: 99%
“…Unlike previous studies investigating prescription practices for Japanese inpatients [1,2], in this study, daily antipsychotics dosage for subjects in Tokyo was not over 1,000 mg chlorpromazine equivalent. This is below the criteria of high-dosing [20]; for maintenance purposes, however, the dosage is relatively high compared with dosage in Western countries. Kane [21] reported that for chronic schizophrenics in clinical research, the average dosage was 385 mg chlorpromazine equivalent.…”
Section: Discussionmentioning
confidence: 91%